Discussion of ‘Style’ from Max Loehr and the Study of Chinese Bronzes, Style and Classification in the History of Art, Ithaca, Cornell University Press: Cornell East Asia Series 2008 - Robert Bagley (Journal of Art Historiography, 2010)
This essay is the concluding chapter of a study of the work of Max Loehr (1903-1988), an art historian whose visual analysis of unprovenanced Chinese bronzes famously anticipated the discoveries of archaeologists. It argues that Loehr’s strictly pragmatic understanding of style is implicit in the daily practice of most art historians, but that most of our explicit uses of the word, including such everyday expressions as ‘Romanesque style’ and ‘style of Raphael’, presume the existence of a mysterious, indefinable entity that is both a property of the object and a disembodied agent evolving independently of artists and objects. Not surprisingly, no procedure for ascertaining the style of an object has ever been described. The failure to recognize that style is not a physical property but only a shorthand for talking about comparisons is responsible for many classic confusions in art history. Finding the causes of a style or explaining its evolution (‘the origin of the Gothic style’, ‘the evolution from Renaissance to Baroque’), relating styles to times or cultures or nations, relating them across media (‘Baroque painting’ and ‘Baroque music’)—these are fictitious problems, artefacts of a mistaken belief in a thing called ‘style’.